Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/ja507346t
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of a Nonheme Iron(IV)–Oxo Complex That Mediates Aromatic C–F Hydroxylation

Abstract: The synthesis of a pentadentate ligand with strategically designed fluorinated arene groups in the second coordination sphere of a nonheme iron center is reported. The oxidatively resistant fluorine substituents allow for the trapping and characterization of an FeIV(O) complex at −20 °C. Upon warming of the FeIV(O) complex, an unprecedented arene C–F hydroxylation reaction occurs. Computational studies support the finding that substrate orientation is a critical factor in the observed reactivity. This work not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
76
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 32 publications
(18 reference statements)
12
76
0
Order By: Relevance
“…The 4.2 K/53 mT Mössbauer spectrum of 1-O displays a quadrupole doublet with parameters ( δ = 0.03 mm/s and Δ E Q = 0.54 mm/s) identical to those previously reported. 33 While the isomer shift is typical of ferryl complexes, the absolute magnitude of the quadrupole splitting parameters is smaller than those observed for other ferryl complexes (Δ E Q ≈ 1.2 mm/s). 36 However, spectroscopic parameters calculated using density functional theory (DFT) methods on geometry-optimized structures of 1-O and the extensively characterized intermediate-spin ferryl complex with 1,4,8,11-tetramethylcyclam ligand [(TMC)Fe IV (O)(CH 3 CN)] 2+ are in good agreement with the experimentally observed values (Table S1).…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…The 4.2 K/53 mT Mössbauer spectrum of 1-O displays a quadrupole doublet with parameters ( δ = 0.03 mm/s and Δ E Q = 0.54 mm/s) identical to those previously reported. 33 While the isomer shift is typical of ferryl complexes, the absolute magnitude of the quadrupole splitting parameters is smaller than those observed for other ferryl complexes (Δ E Q ≈ 1.2 mm/s). 36 However, spectroscopic parameters calculated using density functional theory (DFT) methods on geometry-optimized structures of 1-O and the extensively characterized intermediate-spin ferryl complex with 1,4,8,11-tetramethylcyclam ligand [(TMC)Fe IV (O)(CH 3 CN)] 2+ are in good agreement with the experimentally observed values (Table S1).…”
Section: Resultsmentioning
confidence: 81%
“…33 Upon warming, this complex readily converted to the arene hydroxylated product 1-OAr as shown in Scheme 1, and time-dependent studies confirmed 1-O was the reactive intermediate in this rare C–F hydroxylation reaction. Given the novel reactivity of this Fe IV (O) complex, we were motivated to obtain the complete structural and electronic characterization of this complex by X-ray crystallography and variable-field Mössbauer spectroscopy.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations